Manipulation of magnetic nanostructures through low temperature metal-oxygen chemistry: Co/CoO exchange biased nanodonuts and Co nanotips - Phase, Deodatta; Choudhary, Ram Janay; Ganesan, V.; Reddy, V. Raghvendra; Gupta, Ajay; Selvi, N.; Kulkarni, Sneha; Ogale, Satishchandra (Solid State Communications, 2009)
Dense nanodonut and nanotip type morphologies are shown to self-evolve in Ultrathin cobalt films during growth under Vacuum, depending oil the level of oxygen incorporation and temperature. The nanodonut morphology forms at room temperature and the corresponding magnetic hysteresis shows exchange bias (similar to 35 Oe shift along the field axis), which is attributed to the presence of CoO and its exchange Coupling with cobalt. The morphology evolves into nanotip features with increase of growth temperature, with Concurrent elimination of the oxide component and exchange bias. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Co/CoO; Magnetic film; self assembly; Vacuum evaporation

Algal biomass-loaded hydrogel scaffolds as a biomimetic platform with antibacterial and wound healing activities - Agarwal, Aakanksha; Kumar, Arun; Garg, Piyush; Chakraborty, Arnab; Verma, Ranjan; Sarwat, Maryam; Gupta, Ajay; Sasmal, Pijus K.; Verma, Yogesh Kumar; Chowdhury, Chiranjit; Mukherjee, Monalisa (ACS Applied Polymer Materials, 2022)
The confluence of hydrogel scaffolds and dried algal biomass (AB), consisting of all the bioactive compounds, offers the possibility to facilitate wound healing while simultaneously instilling antibacterial benefits. For this purpose, a single-step synthesis of algal (Chlorella sorokiniana) biomass-loaded hydrogel scaffolds (AHS) was achieved. C. sorokiniana has been used in different areas for several years and has proved attractive to the pharmaceutical and cosmetic industries. Of note, the presence of phytochemicals and various bioactive compounds provides an added health benefit. Hitherto, we report AHS with accelerated wound healing along with potent anti-inflammatory and antibacterial properties. AHS consisting of different concentrations of AB was applied for 14 days on excisional wounds in mice. Microscopic analyses, assessment of proinflammatory and anti-inflammatory cytokines, and histological studies were performed to investigate wound healing. These scaffolds were extensively characterized and studied using Fourier transform infrared, X-ray diffraction, Raman, atomic force microscopy, transmission electron microscopy, scanning electron microscopy, swelling, rheological, thermal, and mechanical analyses. AHS have excellent biocompatibility in addition to significant antibacterial activity against Escherichia coli (99%) and Staphylococcus aureus (98%). We believe that the as-synthesized AHS have the potential to broaden the arsenal of more effective wound healing processes along with antibacterial activities.
Keywords: antibacterial activity; Biomass; hydrogel scaffold; microalgae; wound Healing